2017
DOI: 10.1088/1742-6596/833/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Diabatic models with transferrable parameters for generalized chemical reactions

Abstract: Abstract. Diabatic models applied to adiabatic electron-transfer theory yield many equations involving just a few parameters that connect ground-state geometries and vibration frequencies to excited-state transition energies and vibration frequencies to the rate constants for electrontransfer reactions, utilizing properties of the conical-intersection seam linking the ground and excited states through the Pseudo Jahn-Teller effect. We review how such simplicity in basic understanding can also be obtained for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 118 publications
0
20
0
Order By: Relevance
“…53,54 For the ammonia inversion reaction, the NH symmetric bonding ( A ), nonbonding (n), and symmetric antibonding (* A ) orbitals are specified by valence-bond theory, neglecting the degenerate bonding ( E ) and antibonding (* E ) valence orbitals, whilst for benzene the doubly degenerate HOMO and LUMO orbitals are required. For ammonia, we have found that  A is only weakly involved and so can be ignored in the simplest diabatic approach, 52 justifying this usual and qualitatively very successful practice. 51,55 The n to * A interaction thus generates 3 electronic states (the ground state g, the n* A singly excited state s, and the n* A ,n* A doubly excited state d), all of which are coupled together by the same strong vibronic coupling.…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…53,54 For the ammonia inversion reaction, the NH symmetric bonding ( A ), nonbonding (n), and symmetric antibonding (* A ) orbitals are specified by valence-bond theory, neglecting the degenerate bonding ( E ) and antibonding (* E ) valence orbitals, whilst for benzene the doubly degenerate HOMO and LUMO orbitals are required. For ammonia, we have found that  A is only weakly involved and so can be ignored in the simplest diabatic approach, 52 justifying this usual and qualitatively very successful practice. 51,55 The n to * A interaction thus generates 3 electronic states (the ground state g, the n* A singly excited state s, and the n* A ,n* A doubly excited state d), all of which are coupled together by the same strong vibronic coupling.…”
Section: Introductionmentioning
confidence: 56%
“…A similar but more complex scenario arises also for benzene for which 7 coupled electronic states are implicated. 52 Having established the importance of including all states in quantitative analyses, we also showed that such complex 20 descriptions can be reduced to effective two-state models. This makes available the wide range of results developed for electrontransfer theory and widely applied historically to more general problems, except that now the two-state model parameters become renormalized in a property-dependent fashion.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations